Exploring the value of a well-established conditioned pain modulation paradigm in women: a Translational Research in Pelvic Pain (TRiPP) study - Demetriou, Lysia; Perro, Danielle; Coxon, Lydia; Krassowski, Michal; Lunde, Claire E.; Ferreira-Gomes, Joana; Charrua, Ana; Abreu-Mendes, Pedro; Arendt-Nielsen, Lars; Aziz, Qasim; Birch, Judy; Garbutt, Kurtis; et al. (Frontiers in Pain Research, 2025)
BackgroundConditioned pain modulation (CPM) is considered a human proxy for descending inhibitory pain pathways. However, there is wide variation in the CPM response described in the literature and ongoing debate about its utility. MethodsHere we explored CPM in women with (n = 59) and without (n = 26) chronic pelvic pain (CPP), aiming to determine the magnitude of effect and factors influencing variability in the CPM response.ResultsUsing a pressure pain threshold test stimulus and ischaemic pressure cuff conditioning stimulus (CS), we found no significant difference in the mean CPM effect between CPP and control participants. Using a robust statistical method (+/−2 standard error of measurement) to further investigate CPM, there was no significant difference in the proportion exhibiting inhibition between controls and CPP participants (X2 = 0.003, p = 0.96). Notably, only 23.1% of our healthy controls demonstrated a “true” CPM effect (n = 4 inhibitory, n = 2 facilitatory). Despite a rich data set, we were unable to identify any single questionnaire, clinical or psychophysical covariate correlating with the CPM effect.ConclusionsDespite using one of the recommended CPM paradigms we were only able to demonstrate “true” CPM in 23.1% of control participants. Thus, the absence of differences between women with and without chronic pelvic pain must be interpreted with caution. Future studies using different CPM paradigms or larger sample sizes may find different results. Although CPM in chronic pain populations is of major theoretical mechanistic interest, the lack of an established assessment standard led us to question its added value in current clinical research.